Mobile learning application: Infusing critical thinking in the EFL classroom. - Noni Agustina; Ilza Mayuni; Ifan Iskandar; Ni Made Ratminingsih (Universitas Syiah Kuala, 2022)
The emergence of mobile learning applications facilitates the pedagogical approach to developing students’ critical thinking. However, there is a scarcity of investigation on mobile learning applications’ impact on developing critical thinking as the learning outcome. Thus, this study reports the effect of a mobile learning application, ‘English with Noni’, designed to infuse critical thinking instruction in EFL classes on students’ critical thinking level by employing a sequential explanatory mixed-method approach. A quasi-experimental study was conducted to examine the critical thinking level of 65 students of a junior high school in Jakarta, Indonesia, by administering a post-test assessed using a SOLO rubric. Semi-structured interviews to explore students’ responses from using the ‘English with Noni’ application and class observation contributed to the qualitative findings. The quantitative result showed that the critical thinking level of the experimental group using this application improved significantly more than the controlled group did. The qualitative result suggested that the experimental group had positive responses to using it. They confirmed that it was interesting. They also admitted that it contributed to developing their critical thinking (i.e., predicting, providing reasons, expressing viewpoints, finding alternatives, and making conclusions), language skills (i.e., listening, reading, and writing), and sub-skill (vocabulary). The findings imply that critical thinking activities and learning affordances provided in the ‘English with Noni’ application is a potential tool to enhance students’ critical thinking infused in the EFL class, especially during the COVID-19 pandemic situation, by emphasizing self-regulated learning.